Activation of the bile acid receptor GPBAR1 protects against gastrointestinal injury caused by non‐steroidal anti‐inflammatory drugs and aspirin in mice. (18th December 2012) - Cipriani, Sabrina; Mencarelli, Andrea; Bruno, Angela; Renga, Barbara; Distrutti, Eleonora; Santucci, Luca; Baldelli, Franco; Fiorucci, Stefano
<x xml:space="preserve">Abstract</x> Background and Purpose Low doses of aspirin (acetylsalicylic acid; ASA) and non‐steroidal anti‐inflammatory drugs (NSAIDs) increase the risk of gastrointestinal bleeding. GPBAR1 is a bile acid receptor expressed in the gastrointestinal tract. Here, we have investigated whether GPBAR1 was required for mucosal protection in models of gastrointestinal injury caused by ASA and NSAIDs. Experimental Approch GPBAR1+/+ and GPBAR1−/− mice were given ASA (10–50 mg.kg−1) or naproxen. Gastric and intestinal mucosal damage was assessed by measuring lesion scores. Key Results Expression of GPBAR1, mRNA and protein, was detected in mouse stomach. Mice lacking GPBAR1 were more sensitive to gastric and intestinal injury caused by ASA and NSAIDs and exhibited a markedly reduced expression of cystathionine‐γ‐liase (CSE), cystathionine‐β‐synthase (CBS) and endothelial NOS enzymes required for generation of H2S and NO, in the stomach. Treating GPBAR1+/+ mice with two GPBAR1 agonists, ciprofloxacin and betulinic acid, rescued mice from gastric injury caused by ASA and NSAIDs. The protective effect of these agents was lost in GPBAR1−/− mice. Inhibition of CSE by DL‐propargylglycine completely reversed protection afforded by ciprofloxacin in wild type mice, whereas treating mice with an H2S donor restored the protective effects of ciprofloxacin in GPBAR1−/− mice. Deletion of GPBAR1 altered the morphology of the small intestine and increased sensitivity to injury caused by naproxen. Conclusion and Implications GPBAR1 is essential to maintain gastric and intestinal mucosal integrity. GPBAR1 agonists protect against gastrointestinal injury caused by ASA and NSAIDs by a COX‐independent mechanism.